Effects of chronic and acute zinc sulphate supplementation on myocardial ischemia-reperfusion injury in rats - Ozyildirim, Serhan; Baltaci, Abdulkerim Kasim; Sahna, Engin; Mogulkoc, Rasim; Ergene, Neyhan (Wiley-Blackwell, 2015)
[Abstract Not Available]